The Principal’s Role in Improving Learning Quality Through a Deep Learning Approach at SD Negeri Gerjen, Kulon Progo Regency - Sriyaningsih; Welius Purbonuswanto; Rahmat Mulyono (Universitas Pakuan, 2026)
This study aims to analyze the role of the principal in improving the quality of learning through a deep learning approach in elementary schools. Deep learning, as a learning method based on deep understanding, collaboration, and the application of concepts in real-world contexts, requires effective leadership support. The research method employed a qualitative approach with data collection techniques through interviews, observations, and document studies. The findings indicate that the principal acts as an instructional leader through the following strategies: (1) facilitating teacher training on deep learning, (2) creating a collaborative learning environment, (3) optimizing school resources, and (4) monitoring competency-based learning evaluation. As a result, teachers become more skilled in designing meaningful learning experiences, while students demonstrate improvements in critical thinking skills and creativity. This study concludes that the principal’s leadership is the key to the successful implementation of deep learning for high-quality learning.